The Boundary Case of the $J$-Flow (Journal of Mathematical Study, 2024)
In this paper, we shall study the boundary case for the J-flow under certaingeometric assumptions.
Keywords: $J$-flow; Monge-Ampère type; cone condition; boundary case; pluripotential solution.